1981
DOI: 10.3109/00498258109045871
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic fate of [3H]econazole in man

Abstract: 1. Following single oral doses of 3[H]econazole base (500 mg) to two human subjects, excretion of radioactivity was prolonged, and incomplete after five days (means of 40% and 27% dose in urine and faeces respectively). 2. Plasma concn. of unchanged econazole and total radioactivity attained peak values at approx. the same for each subject (1.5 - 3h), but the former declined much faster than the latter. Most of the 3H in early plasma samples was present as unchanged drug and extractable metabolites, but after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…During this study, two oxidative metabolites of the imidazole ring of DY-9760e were identified. Similar oxidation of the imidazole ring moiety has been reported for ketoconazole, econazole, nafimidone, and croconazole (Midgley et al 1981;Girkin et al 1983;Nakano et al 1989;Rush et al 1990;Whitehouse et al 1994). Two oxidative metabolites of the imidazole ring of ketoconazole were found in mouse liver after oral administration.…”
Section: Discussionsupporting
confidence: 57%
“…During this study, two oxidative metabolites of the imidazole ring of DY-9760e were identified. Similar oxidation of the imidazole ring moiety has been reported for ketoconazole, econazole, nafimidone, and croconazole (Midgley et al 1981;Girkin et al 1983;Nakano et al 1989;Rush et al 1990;Whitehouse et al 1994). Two oxidative metabolites of the imidazole ring of ketoconazole were found in mouse liver after oral administration.…”
Section: Discussionsupporting
confidence: 57%
“…Econazole (Fig. 7) undergoes the imidazole oxidations into the 2,4-dioxo-, 2-hydroxy-5-oxo-and 2,5-dioxo derivatives in humans and excreted in the urine as glucuronides after the O-dealkylations 46) .…”
Section: Placements Of Imidazole Fungicidesmentioning
confidence: 99%
“…39 Despite showing promising activity in vitro against each of these diseases, oral and intravenous administration have proven ineffective due to the poor pharmacokinetics of the drug, which has no gastrointestinal absorption, and rapidly undergoes metabolism and protein binding in the blood stream. 36,40 As such, a prodrug system capable of increasing the effective dose of econazole could be beneficial to the treatment of a number of conditions. Ruthenium complexes with 1 or 2 econazole ligands were prepared in a single step in moderate yield from reaction of econazole nitrate with [Ru(phen) 2 Cl 2 ] (phen = 1,10phenanthroline).…”
mentioning
confidence: 99%
“…This is encouraging for the development of a prodrug of econazole as the free drug is rapidly metabolized to inactive products in vivo. 36,40 The photolytic stability of the complexes was monitored by UV-visible absorbance and emission spectroscopy, and mass spectrometry. An aqueous solution of 2 was irradiated with green light (520 nm) for 1 h (53 J cm -2 ) and changes in its spectra monitored over time.…”
mentioning
confidence: 99%